2016
DOI: 10.1021/acs.langmuir.5b03873
|View full text |Cite
|
Sign up to set email alerts
|

Surface Charge at the Oxide/Electrolyte Interface: Toward Optimization of Electrolyte Composition for Treatment of Aluminum and Magnesium by Plasma Electrolytic Oxidation

Abstract: Controlling microdischarges in plasma electrolytic oxidation is of great importance in order to optimize coating quality. The present study highlights the relationship between the polarity at which breakdown occurs and the electrolyte pH as compared with the isoelectric point (IEP). It is found that working at a pH higher than the IEP of the grown oxide prevents the buildup of detrimental cathodic discharges. The addition of phosphates results in a shift in the IEP to a lower value and therefore promotes anodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 23 publications
1
17
0
1
Order By: Relevance
“…The presence of cathodic discharge on Aluminium surface at a pH significantly higher than the isoelectric point (IEP) may appear at first sight surprising and somehow contradictory with some published results [23]. On the other hand, the fact that the presence of cathodic discharges is triggered at high frequency (above 2 kHzsee fig.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…The presence of cathodic discharge on Aluminium surface at a pH significantly higher than the isoelectric point (IEP) may appear at first sight surprising and somehow contradictory with some published results [23]. On the other hand, the fact that the presence of cathodic discharges is triggered at high frequency (above 2 kHzsee fig.…”
mentioning
confidence: 70%
“…However, recent studies have shown the possibility to observe micro-discharges under cathodic polarization, both on Magnesium [20][21][22][23] and Aluminum [23,24] substrates either by using uncommon compositions of electrolytes [20,21] or by applying high-current density (several kA dm −2 ) [24]. A subsequent study in similar conditions to reference [20] has shown that cathodic discharges do not take part in the growth of an oxide coating and rather have detrimental effect on it [22].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…31 The vigorous plasma discharges further facilitated the incorporation of Ni(OH) 2.4 0.4À into the inorganic layer. Ni , and H 2 O to produce Ni(OH) 2 , as shown in eqn (6). The instantaneous high temperature and pressure around the discharge channels during the PEO process led to partial the oxidation of Ni(OH) 2 to form NiO, as described in eqn (8).…”
Section: 67mentioning
confidence: 99%
“…6 The characteristics of the inorganic layer formed by the PEO process are affected by the plasma characteristics (size, density, intensity, and duration), which can be controlled by the electrolyte conditions, e.g. its chemical composition, and the processing variables, such as electrical parameters, including current density, frequency, and current mode.…”
Section: 3mentioning
confidence: 99%